Mitochondrial transplantation as a promising therapy for mitochondrial diseases - Tian-guang Zhang; Chao-yu Miao (Elsevier, 2023)
Mitochondrial diseases are a group of inherited or acquired metabolic disorders caused by mitochondrial dysfunction which may affect almost all the organs in the body and present at any age. However, no satisfactory therapeutic strategies have been available for mitochondrial diseases so far. Mitochondrial transplantation is a burgeoning approach for treatment of mitochondrial diseases by recovery of dysfunctional mitochondria in defective cells using isolated functional mitochondria. Many models of mitochondrial transplantation in cells, animals, and patients have proved effective via various routes of mitochondrial delivery. This review presents different techniques used in mitochondrial isolation and delivery, mechanisms of mitochondrial internalization and consequences of mitochondrial transplantation, along with challenges for clinical application. Despite some unknowns and challenges, mitochondrial transplantation would provide an innovative approach for mitochondrial medicine.